VITAMIN B 12 AND HOMOCYSTEINE LEVELS IN PRIMI GRAVIDA PATIENTS WITH PRE-ECLAMPSIA: AN EXPERIENCE FROM A TERTIARY CARE HOSPITAL OF PAKISTAN - Bawar, Shandana; Firdous; Shafqat , Tanveer; Rubina Nazli (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the frequency of serum vitamin B12 and homocysteine levels in patients with Pre-eclampsia. Methodology: This cross-sectional study was carried out in Department of Gynecology and Obstetrics, Lady Reading Hospital, Peshawar in collaboration with the Department of Biochemistry of Khyber Medical University (KMU), from May 2019 to December 2019 after obtaining ethical approval from Advanced Study and Research Board (ASRB). Using non-probability convenient sample technique, 60 patients who were Primi Gravida with Pre-eclampsia were admitted via OPD or labour room. Data was collected from hospital record , charts and documented and analyzed in SPSS version 22. Results: The mean age of the patients in this study was 21.75 ± 2.05 years. The mean vitamin B 12 levels recorded in our study was 175 ± 34.39 pmol/l. Vitamin B 12 levels in most of the participants, 45(75%) were in normal ranges. 12(20%) patients were deficient in vitamin B 12 levels while 03(05%) patients had high levels of vitamin B12. The mean serum Homocysteine level in our study was 9.63 ± 3.46 umol/l. Most of the participants 48 (80%) had normal levels while 09(15%) patients had high levels of serum Homocysteine while only 03 (05%) patients were deficient in serum Homocysteine levels. Conclusion: Majority of the patients with Pre eclampsia had normal levels of Homocysteine and vitamin B12. There was an inverse correlation between serum Vitamin B12 and Homocysteine levels in Pre-eclamptic patients